Enhancing cysteine content in yogurt - Soumya Bala; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 2011)
Cysteine is considered a conditional amino acid for certain subpopulations. For example, in elderly people, cysteine has been associated with diverse functional properties as a general antioxidant as well as a specific role linked to cataract reduction or prevention. Yogurt is an excellent source of protein, the sulfur-containing amino acids methionine and cysteine in particular. Heat, however, can denature these amino acids and affect their bioavailability. A yogurt mix supplemented with whey proteins (an abundant source of cystiene) coupled with minimal pasteurization of yogurt mixes may increase the availability of cysteine in the final product. In this study, yogurt mixes were supplemented with nonfat dry milk (NDM) or whey protein isolate (WPI; 90% protein), processed at 90oC for 7 minutes or 70oC for 20 minutes, then fermented into yogurt following a conventional procedure. Supplementing yogurt mix with WPI vs. NDM increased cysteine content by 140%. In contrast, overall cysteine contents decreased by 17% in mixes treated at 70oC for 20 minutes and 35% in mixes treated at 90oC for 7 minutes. Mixes supplemented with WPI and treated at 70oC for 20 minutes produced yogurts that had greater cysteine contents and slightly greater firmness and water-holding capacity, but the yogurts exhibited less syneresis compared with those made from mixes supplemented with NDM and treated at 90oC for 7 minutes. These results indicate that yogurt may be an excellent delivery vehicle for the conditional amino acid, cysteine.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Dairy; Yogurt; Cysteine; Heat treatment